PENGARUH HUTANG JANGKA PANJANG TERHADAP RETURN ON INVESTMENT PADA PT KALBE FARMA, Tbk. - Adha Indriani, Novi; Anggriani, Susan; Eriswanto, Elan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of long-term debt on the return on investment (ROI) at PT Kalbe Farma Tbk. Variables used in this study is the long-term debt as the independent variable and the return on investment (ROI) as the dependent variable. The research method used is descriptive associative with a quantitative approach. The sample used is the quarterly financial statements of PT Kalbe Farma Tbk is listed on the Indonesia Stock Exchange, the number of samples in this study there were 36 samples.